Combination of Immune Checkpoint Inhibitors and Radiotherapy for Advanced Non-Small-Cell Lung Cancer and Prostate Cancer: A Meta-Analysis. (5th January 2021) - Xu, Zexi; Feng, Jia; Weng, Yiming; Jin, Yao; Peng, Min
Abstract : Objectives . Immune checkpoint inhibitors (ICI) combined with radiotherapy (RT) have emerged as a breakthrough therapy in the treatment of various cancers. The combination has a strong rationale, but data on their efficacy and safety are still limited. Hence, we comprehensively searched the database and performed this study to elucidate the clinical manifestations of this combined strategy. Methods . We performed a meta-analysis of randomized trials that compared ICI plus RT with placebo plus RT or ICI alone for the treatment of advanced nonsmall-cell lung cancer (NSCLC) and prostate cancer. The outcomes included overall survival (OS), progression-free survival (PFS), disease control rate (DCR), and treatment-related adverse events. A fixed-effects or random-effects model was adopted depending on between-study heterogeneity. Results . Three trials involving 1584 patients were included. ICI plus RT was significantly associated with improvement of OS (hazard ratio [HR] = 0.81, 95% confidence interval [CI] = 0.70–0.94, P = 0.004 ), PFS (HR = 0.64; 95% CI 0.56–0.72, P < 0.00001 ), and DCR (relative risk [RR] = 1.38; 95% CI 1.03–1.84, P = 0.03 ). A significant predictor for PFS with the combination of ICI and RT was age, as a significant improvement in PFS (HR = 0.49; 95% CI 0.37–0.64, P < 0.00001 ) was observed in NSCLC patients aged under 65 years. In safety analyses, patients receiving ICI plus RT had a significantly higher incidence of dyspnea (RR = 2.43; 95% CI 1.16–5.08, P = 0.02 ) and pneumonitis of grade 3 or higher (RR = 2.78; 95% CI 1.32–5.85, P = 0.007 ). Conclusion . The combination of ICI and RT was associated with improved OS, PFS, and DCR. Patients under 65 years will be the dominant beneficiaries. However, the incidence of dyspnea and pneumonia of grade 3 or higher also increased, which deserves our vigilance.